Chelation of hippocampal zinc enhances long‐term potentiation and synaptic tagging/capture in CA1 pyramidal neurons of aged rats: implications to aging and memory. Issue 1 (16th September 2016) - Shetty, Mahesh Shivarama; Sharma, Mahima; Sajikumar, Sreedharan
Summary: Aging is associated with decline in cognitive functions, prominently in the memory consolidation and association capabilities. Hippocampus plays a crucial role in the formation and maintenance of long‐term associative memories, and a significant body of evidence shows that impairments in hippocampal function correlate with aging‐related memory loss. A number of studies have implicated alterations in hippocampal synaptic plasticity, such as long‐term potentiation (LTP), in age‐related cognitive decline although exact mechanisms underlying are not completely clear. Zinc deficiency and the resultant adverse effects on cognition have been well studied. However, the role of excess of zinc in synaptic plasticity, especially in aging, is not addressed well. Here, we have investigated the hippocampal zinc levels and the impairments in synaptic plasticity, such as LTP and synaptic tagging and capture (STC), in the CA1 region of acute hippocampal slices from 82‐ to 84‐week‐old male Wistar rats. We report increased zinc levels in the hippocampus of aged rats and also deficits in the tetani‐induced and dopaminergic agonist‐induced late‐LTP and STC. The observed deficits in synaptic plasticity were restored upon chelation of zinc using a cell‐permeable chelator. These data suggest that functional plasticity and associativity can be successfully established in aged neural networks by chelating zinc with cell‐permeable chelating agents.